Knowledge and skills toward capnometry and capnography among Emergency Medical Service providers - Czyż, Rafał; Leśkiewicz, Marcin; Czyż, Izabela (Journal of Education, Health and Sport, 2018)
Capnometry is an increasingly used element of patient monitoring in emergency medicine, also in pre-hospital area. The increasing availability of compact devices for measuring the end-expiratory concentration of carbon dioxide (EtCO2) offers great opportunities to improve the quality of treatments, as well as giving rescuers feedback on the effectiveness of life-saving procedures. However, the capnometer is just another device and without the proper substantive preparation of the person who uses it, its usefulness will be negligible. Aim of this study, is to assess paramedics knowledge about capnometry and capnography. The study group consisted of 102 paramedics who are actively working in ambulance service, aged 30.5 ± 5.7 years including 7% of women and 93% of men. Results were collected with the author’s questionnaire. Most of participants (91%) confirmed that in their ambulance was available device to measure end-expiratory carbon dioxide (EtCO2). The most commonly available device was capnometry (72%), followed by the capnography (19%). Moreover, the analysis shows that the rescuers who declared participation in the training of monitoring and analysis end-expiratory value of carbon dioxide concentration in the last 12 months obtained significantly higher correct answers than the staff who did not have such training (6.5 ± 2.0 vs. 5.4 ± 1.7). However, only 35% of participants took part in such training in last year.Study shown a lack of knowledge and experience in use of devices to measure end-expiratory carbon dioxide concentration (EtCO2) by Emergency Medical Service providers.